INFORMASI PENGISIAN BATERAI KENDARAAN SEPEDA MOTOR LISTRIK BERBASIS INTERNET OF THINGS (IOT) - Artayuda, Rizky; Candra, Robby; Rasjid, Hasma; Chalri, Yulia (Jurnal Informatika, 2025)
The main problem faced in the use of electric motorcycles is the lack of information in the process of charging the electric motorcycle battery which can have an impact on the costs incurred when charging the electric motorcycle battery. The purpose of this study is for electric motorcycle owners to obtain information such as voltage, current, power, and energy consumed as well as an estimate of the cost of charging the battery in real time while their electric motorcycle is being charged. The methods used include the use of the INA219 sensor to measure electrical parameters, the TP4056 module for charging, and the Wemos D1 Mini ESP8266 to process data and send information to the Blynk platform. The data obtained is displayed on a 16x2 LCD and sent to the Blynk application for remote monitoring. The results obtained can display information on voltage, current, power, and energy consumed as well as an estimate of the cost when charging the electric motorcycle battery via the LCD. This information can also be viewed via a smartphone using the Blynk application so that electric motorcycle users can still get information related to battery charging.